3T MRI of Peripheral Vascular Malformations: Characteristics and Comparison of Two Fat-Saturated sequences: Short Tau Inversion Recovery Versus Three-Dimensional High-Resolution Volume Interpolated Gradient Recalled Echo - Höhn, Florentine; Hammer, Simone; Fellner, Claudia; Zeman, Florian; Uller, Wibke; Brill, Richard; Guntau, Moritz; Wildgruber, Moritz; Wohlgemuth, Walter A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To assess morphological and hemodynamic characteristics of peripheral vascular malformations on 3 T magnetic resonance imaging (MRI) including qualitative comparison of two fat-saturated sequences: short tau inversion recovery (STIR) and three-dimensional high-resolution volume interpolated gradient recalled echo (GRE).Materials and Methods During 9 months, 100 patients with suspected or known vascular malformations were prospectively assessed on a 3 T scanner using T2-weighted STIR and turbo spin echo (TSE), T1-weighted TSE, time-resolved contrast-enhanced magnetic resonance angiography (MRA) with interleaved stochastic trajectories (TWIST) and T1-weighted volume interpolated breath-hold examination (VIBE) after contrast enhancement. The analysis included signal behavior and morphologic and hemodynamic characteristics. Additionally, the image quality of the fat-saturated sequences was evaluated by 2 radiologists.Results 86 patients (14 dropouts; 57 female, 29 male; mean age 26.8 years, age range 1–56) were analyzed. 22 had high-flow and 64 low-flow malformations, including 14 with a lymphatic component. In 21 of 22 patients with high-flow malformations, typical characteristics (flow voids, hyperdynamic arteriovenous fistula, dilated main/feeder-arteries and draining veins) were documented. Patients with low-flow malformations had phleboliths in 35 cases, fluid-fluid levels in 47 and dilated draining veins in 23. Lymphatic malformations showed peripheral contrast enhancement of cyst walls in the volume interpolated GRE. The comparison of fat-saturated sequences showed significantly better results of the volume interpolated GRE in all categories except the presence of artifacts which were significantly reduced in the STIR (p < 0.05).Conclusion 3 T MRI with MRA provides detailed morphological and hemodynamic information of different types of peripheral vascular malformations. Contrast-enhanced high-resolution volume interpolated GRE proved superior to STIR in differentiating morphologic features and to be diagnostic in the differentiation of lymphatic parts and joint involvement.Key Points: Citation Format
Keywords: peripheral vascular malformation; magnetic resonance imaging (MRI); short tau inversion recovery (STIR); volume interpolated breath-hold examination (VIBE); 3.0 Tesla; morphologic characteristics